Hydroclimatology : perspectives and applications - Shelton, Marlyn L. (Cambridge University Press, 2009)
"Hydroclimatology provides a systematic structure for analysing how the climate system causes time and space variations (both global and local) in the hydrologic cycle. Changes in the relationship between the climate system and the hydrologic cycle underlie floods, drought and possible future influences of global warming on water resources. Land-based data, satellite data, and computer models contribute to our understanding of the complex time and space variations of physical processes shared by the climate system and the hydrologic cycle." "Blending key information from the fields of climatology and hydrology - wich are not often found in a single volume - this is an ideal textbook for students in atmospheric science, hydrology, Earth and environmental science, geography, and environmental engineering. It is also a useful reference for academic researchers in these fields."--Jacket